Intention to Adopt Blockchain-Based Technologies: A Systematic Literature Review - Husam Abdulhameed Hussein (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Blockchain technologies have garnered significant attention from both industry as well as academia due to their unique features, including data, security, integrity, reliability and decentralization. Despite this, their adoption remains limited, prompting many studies to explore their user satisfaction and adoption rates. Understanding a factors influencing to the intention to adopt blockchain can help address these challenges. Numerous SLRs have reviewed studies for advancing knowledge, identifying research priorities, and informing decision-making in academic and practical contexts. These studies span blockchain technology across diverse fields, including energy management, healthcare, and logistics. Some review delves into its technical aspects, like algorithms and cryptography, while others explore legal frameworks. However, prior research on factors influencing the intention to adopt blockchain-based technologies is limited, and the current research trend remains ambiguous. To bridge the gap, this study aims to comprehensively examine existing research on blockchain-based technology adoption and discuss the challenges and opportunities across deferent sectors, of 225 collected papers, 28 empirical studies that met the criteria and underwent thorough analysis. Findings indicate that the Technology Acceptance Model (TAM) and Technology-Organization-Environment (TOE) are commonly used frameworks for studying blockchain adoption, and in addition to the core variables of these models, perceived cost, trust, facilitating conditions and social influence emerged as the most investigated determinants on various blockchain-based applications. Supply chain management emerges as the primary domain for blockchain adoption. Adoption and continuing to adopt or use are the focus of many studies. Furthermore, existing studies predominantly focus on individual adoption, with little attention given to organizational-level adoption. However, there is limited research on the intention to adopt. This SLR is suppose improve the our understanding by revealer blockchain's full potential, opening the door for the further opportunities of research.